THE USE OF SNOWBALLING TECHNIQUE TO LEARN APPLYING VOCABULARY AFTER THE PANDEMIC THE USE OF SNOWBALLING TECHNIQUE TO LEARN APPLYING VOCABULARY AFTER THE PANDEMIC - Setianingsih, Tri; Qomariyah, Siti Syafi’atul; Nafisah, Bq. Zuhrotun (Lembaga Penelitian dan Pendidikan Mandala, 2021)
The Use of Snowballing Technique to Learn Applying Vocabulary After the Pandemic. This research is aimed at finding out the effectiveness of using snowballing technique to learn applying vocabulary at the third grade students of SMAN 1 Batulayar in academic year 2020/2021. This research is an experimental research with quasi experimental and category of this research is non-equivalent control group design. The population of this research is the third grade students of SMAN 1 Batulayar consist of 62 students. The instrument that will be used to collect the data is test consists of post-test. The data will be analysed by using statistical formula of t-test.The result of data analysis showed that the value of t-test was 4.39 and t-table 2.00. The value of t-testis higher than t-table in significance level0.05 and degree of freedom 62-2. It meant that t-critical value was significant fot this confidence level. Then, alternative hypothesis (Ha) was accepeted and null hypothesis (Ho) was rejected. It could be concluded that there was an effect of using snowballing technique to teach vocabulary at the third grade students of SMAN 1 Batulayar in Academic year 2021/2022.